Preferences, Proximity, and Controlled Choice: Examining Families' School Choices and Enrollment Decisions in Louisville, Kentucky. Issue 4 (8th August 2018) - Frankenberg, Erica
Abstract : This study provides evidence studying one diverse, countywide district's integration efforts utilizing school choice and parental preferences. The findings illustrate substantial differences about the way in which the district's student assignment policy affects students. In particular, this choice-based integration policy with a weak geographic preference still advantages those who choose their nearest schools as well as white students and those living in more advantaged areas. Examining differences in families' school preferences, whether students are assigned to their preferred school, and whether and where students enroll in schools illustrates how an integration-focused assignment policy can still result in segregation and inequality. Yet, by illustrating the many influences on family preferences beyond proximity, it also suggests the opportunity for using assignment policy to overcome persistent neighborhood segregation.